Kajian Evaluasi Kinerja Jalan Ciawi-Bogor Sebelum Pengembangan PT. ABC - Fadhil, Dimas Nu’man; Suryobuwono, Abdullah Ade; Kristiadi, Aldo; Rahmat, Rahmat; Marpaung, Edward; Sakti, Reza Fauzi Jaya (Institut Transportasi dan Logistik Trisakti, 2021)
Developing factory area require construction activities which impacting traffic surround the area. Before the construction process is carried out, a traffic impact analysis (andalalin) is needed to determine the impact from the development process to operation. The method used in this study process is micro traffic simulation based on the 1997 MKJI method, from the results of the traffic survey the 1997 MKJI calculations were carried out, the total capacity of the Ciawi-Bogor road was 3,146 pcu/hour with the highest traffic volume of 2954 so that the degree of saturation reached 0.93.